Robust disturbance rejection control of helicopter system using intelligent identification of uncertainties - Raafat, Safanah M.; Akmeliawati, Rini (Elsevier, 2012)
This paper addresses the problem of designing a robust control for a laboratory 3DOF helicopter system. Simplified and disturbance rejection robust controllers are presented for the linearized dynamical system. The robust controller is formulated as a mixed H2/H∞ problem. An Adaptive Neuro Fuzzy Inference System (ANFIS) is used for intelligent estimation of uncertainties. This paper is dedicated to robustly compensate for the effects of modelling uncertainties and disturbances on the helicopter system, using intelligent estimation. Further study on the design and controller implementation issues is now being developed.